Case report: mediastinal hydatid cysts. - Ozyurtkan, Mehmet O?uzhan; Koçyi?it, Semih; Cakmak, Muharrem; Ozsoy, Ibrahim Ethem; Balci, Akin Eraslan (My University, 2009)
Although the intrathoracic location is common for hydatid cyst, chest-wall, mediastinal, pericardial, myocardial, fissural and pleural-space locations have been reported. The incidence of mediastinal involvement is 0.1-0.5%. Here in this paper, two cases of mediastinal hydatid cysts are reported. Both of them had anterior mediastinal hydatidosis, while one of the patients had also additional three pericardial hydatid cysts. They have undergone thoracotomy for the removal of cystic lesions. Hydatid cysts should be considered in the differential diagnosis of mediastinal cystic lesions especially in the endemic regions. Surgical removal is the treatment of choice for mediastinal hydatid cysts, and additional medical therapy may avoid recurrence.
Keywords: Adult; Diagnosis, Differential; Echinococcosis; Endemic Diseases; Humans; Male; Mediastinal Diseases; Middle Aged; Pericardium; Recurrence; Splenic Diseases; Turkey; adult; article; case report; differential diagnosis; echinococcosis; echography; endemic disease; human; male; mediastinum disease; middle aged; parasitology; pericardium; recurrent disease; spleen disease; Turkey (republic)